The Influence of β-Carotene and Its Liposomal Form on the Expression of EMT Markers and Androgen-Dependent Pathways in Different Prostate Cell Lines - Joanna Dulińska-Litewka; Kacper Dykas; Stanisław Boznański; Przemysław Hałubiec; Marta Kaczor-Kamińska; Jacek Zagajewski; Torsten Bohn; Gracjan Wątor (MDPI AG, 2024)
Prostate cancer (PCa) is the most common malignancy in men. Although the prognosis in the early stages is good, the treatment of advanced PCa remains a formidable challenge. Even after an initial response to hormone therapy or chemotherapy, recurrences are frequent and resistance to any systemic treatment is common. β-Carotene (BC), a plant-derived tetraterpene, is known for its antioxidant capacity and can modulate multiple cellular signaling pathways, potentially affecting androgen synthesis. We investigated the influence of BC (dissolved in EtOH/THF with a cell culture medium or encapsulated in liposomes (LP-BCs)) on the viability, migration potential, and connective tissue cleavage capabilities of several PCa cell lines (Du145, LNCaP, PC-3, and 22Rv1) and a healthy prostate model (RWPE cells). BC significantly reduced the proliferative capacity of all investigated cell lines at various concentrations (1.5-30 µM) and decreased cell migration. However, it significantly increased the expression of epidermal-mesenchymal transition (EMT) master proteins in all cancer cell lines and RWPE (p < 0.05) These effects were not observed with LP-BCs. This study suggests that LP-BCs, with their higher antiproliferative capabilities and pronounced inhibition of the EMT, may be a more effective form of possible PCa prevention or treatment than the free form. LPs may also modulate lipid metabolism in PCa cells.